(untitled) - Anderson, Sandra K.; Sandra K. Anderson (Albany, N.Y., 1992)
This "hands on" text introduces the student to the computer and applies this knowledge to the health care setting. Numerous examples of specific medical applications of the computer are provided and the latest hardware and software discussed
Keywords: Computer literacy; Medical personnel; Health Occupations